PENGARUH MANAJEMEN PENDIDIKAN BERBASIS TEKNOLOGI INFORMASI DI SEKOLAH DASAR TERHADAP MOTIVASI BELAJAR SISWA - Kamila Syifa Maulida; Risnayanti Annur; Rahadian Rahindra; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
Information technology-based education has become the main focus in efforts to improve the quality of learning at various levels of education, including elementary schools. This research aims to evaluate the influence of information technology-based educational management in elementary schools on student learning motivation. The research method used is an evaluation study with a quantitative approach. Data was collected through questionnaires distributed to elementary school students to measure their perceptions of information technology-based educational management implemented in schools. Apart from that, data regarding the level of student motivation to learn was also obtained through questionnaires. The results of the research show that there is a positive relationship between information technology-based educational management in elementary schools and student learning motivation. Schools that implement educational management that utilizes information technology effectively tend to have higher levels of student learning motivation. Based on these findings, it is recommended that elementary schools continue to improve the implementation of information technology-based educational management. This can be done through training for teachers in utilizing information technology to support learning, developing interactive online learning platforms, as well as providing technical and psychosocial support to students and teachers